Copper matrix composites reinforced by rGO-MoS2 hybrid: Strengthening effect to enhancement of tribological properties - Nautiyal H.; Kumari S.; Khatri O.P.; Tyagi R. (My University, 2025)
The potential of reduced graphene oxide-molybdenum sulfide (rGO-MoS2) hybrid as a self-lubricating reinforcement in the Cu-based composites for enhancement of mechanical and tribological properties is presented. The rGO-MoS2 was synthesized by a hydrothermal approach using highly dispersed graphene oxide as a platform material to grow the MoS2 nanosheets. The Cu-rGO-MoS2 composites having 2 wt% of rGO-MoS2 were prepared at 600, 650, 700 and 750 °C to probe the effect of sintering temperature on mechanical and tribological properties. Microscopic images of Cu-rGO-MoS2 composites based on SEM and HRTEM measurements along with corresponding area elemental distribution suggested the nearly uniform dispersion of rGO-MoS2 hybrid in the copper matrix via multidimensional interactions. The composites exhibited significantly improved hardness compared to pure copper, and it was attributed to freezing of the movement of the dislocations by rGO-MoS2. Incorporation of rGO-MoS2 in Cu resulted in a remarkable reduction in both the coefficient of friction and the wear rate. The improved friction and wear performances of composites have been ascribed to the self-lubricating action of rGO-MoS2 hybrid and the formation of rGO-MoS2 containing tribo-film on the counter face steel ball which facilitated the sliding events and protected the tribo-pair against the wear. © 2019 Elsevier Ltd